Masturbation and its consequences in the light of scientific ideas and empirical data - Коcharyan , G. (Psychological Counseling and Psychotherapy, 2023)
Information is presented on the dynamics of attitudes toward masturbation in relation to changing perceptions about its possible pathogenicity. For many centuries, masturbation was thought to be extremely harmful and such that could lead to the development of many diseases. Over time, attitudes about the severity of the possible negative consequences of masturbation have softened. At first, the most severe ones were excluded, and then, over time, the prevailing view was that masturbation could not lead to any negative results other than feelings of guilt. This article presents the classification of masturbation according to Vasilchenko (1977). The analysis of this classification shows that in the majority of cases it has no negative influence. Moreover, masturbation of the period of youthful hypersexuality promotes sexual development, and vicarious masturbation has a substitute function. At the same time, perseverative-compulsive masturbation is carried out in a mode significantly exceeding the constitutional optimum. The classification of possible adverse effects of masturbation developed by the author of the article is also presented (Kocharyan, 2006, 2007). In our opinion, the combined use of these two classifications of masturbation allows to estimate the possibility of its influence, including pathogenic one, on a human body in complex, because different kinds of masturbation (including of the period of youthful hypersexuality according to Vasilchenko classification) in some cases can have negative influence on a human body (at present mostly through behavioral mechanisms). It is noted that masturbation, however, can also have positive effects. In particular, it is expressed in the fact that it can promote sexual development, perform a compensatory function. It also has an antidepressant and anti-anxiety effect. It is widely used to treat various sexual disorders. Based on the analysis, the author concludes that masturbation should not be excluded from the list of phenomena responsible for the occurrence of human health disorders. Attempts to fully rehabilitate it in this sense are untrue.